2010
DOI: 10.1007/s12032-010-9731-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of combined detection of AFU and TCH in differential diagnosis between malignant and non-tuberculous benign ascites

Abstract: The purpose of this study was to accurately evaluate the diagnostic efficacy of combined detection of ascitic fluid alpha-L-fucosidase (AFU) and cholesterol (TCH) compared with that of their individual detection. We assayed ascitic AFU activity by colorimetry and TCH level by CHOD-PAP method simultaneously in all 213 cases. Then, we assessed the value of combined detection of AFU and TCH activities with receiver operating characteristic curve (ROC curve), including diagnostic sensitivity, specificity, diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Another study showed that AFU in combination with CD26 can form a molecular model for diagnosis, especially for non-disseminated CRC 31. The combination of AFU and TCH can have better diagnostic accuracy in comparison with their individual detection ability, which is helpful for differential diagnosis between malignant and non-tuberculous benign ascites 32. In our study, we found that increased preoperative AFU in peripheral blood can predict better survival in CRLM patients undergoing hepatic resection.…”
Section: Discussionsupporting
confidence: 53%
“…Another study showed that AFU in combination with CD26 can form a molecular model for diagnosis, especially for non-disseminated CRC 31. The combination of AFU and TCH can have better diagnostic accuracy in comparison with their individual detection ability, which is helpful for differential diagnosis between malignant and non-tuberculous benign ascites 32. In our study, we found that increased preoperative AFU in peripheral blood can predict better survival in CRLM patients undergoing hepatic resection.…”
Section: Discussionsupporting
confidence: 53%
“…It is said that no tumor marker has been found with high sensitivity and specificity in the malignant ascites induced by all causes. Some scholars (Zhang et al, 2011) believed that the combined detection of tumor markers in serum and ascites could improve their diagnostic values. This study mainly explored the values of tumor markers in serum and ascites as well as the ratios of ascites/serum in the identification and diagnosis of malignant ascites by analyzing the clinical data of patients diagnosed with ascites in our hospital in recent years.…”
Section: Tumor Markers In Serum and Ascites In The Diagnosis Of Benigmentioning
confidence: 99%
“…11 Papers about the detection of ascitic cholesterol have been published a lot and they have shown a relatively high diagnostic efficiency in differential diagnosis of MRA. 2,3 However, conflicting results have been reported and the exact role of ascitic fluid cholesterol concentration remains unclear.…”
mentioning
confidence: 99%